TINJAUAN YURIDIS TENTANG BADAN KEPEGAWAIAN DAERAH DALAM MEMINIMALISIR TERJADINYA PERCERAIAN BAGI PEGAWAI NEGERI SIPIL DALAM WILAYAH KABUPAEN KUTAI KARTANEGARA - Imelda Theresia P (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT The local management agency is an extension of the regent/mayor's hand which handles management matters on staff. With regard to the issue of divorce permits for civil servants must apply for permission to obtain a divorce issued against the regent/mayor through the personnel agency that will assess whether administrative conditions are met and whether the stated reasons are acceptable in the case of the development of the staff, there is no doubt that the region's management will continue to maintain a divorce, but there must be measures that hope to have the impact of the divorce and try to unify the integrity of the member's family in the hopes of a less severe civil servant's divorce.The study method of empirical legal research means that is assessed as real behavior and as a written social symptom that is experienced in social and environmental relationships.Research shows that the mechanisms and processes of granting a divorce to civil servants are submitted in writing to officials according to a hierarchy by a preliminary process through the head of the job application which, when attempting to reconcile again, the applicant's superior provides a written consideration and suggestion for consideration to the officer who will make the decision, The government's decision to obtain a mandatory divorce was made by officials in order to minimize divorce for the NNS decision on the basis of the application and the application of the state court. Keywords: Regional Employment Agency, Divorce Permits For Civil Servants, Minimize.